Mutual information power analysis attack in the frequency domain of the crypto chip - Min WANG; Zhen WU; Jin-tao RAO; Zhi-bo DU (Tongxin xuebao, 2015)
Based on the mutual information power analysis attack in time domain of the crypto chip,a method for analyzing the energy of the maximum mutual information coefficient in the frequency domain was proposed.This method combined the principle of password chip information leakage in frequency domain and the principle of mutual information power analysis.The concept of maximum mutual information coefficient was introduced,which avoided the operation of accurate alignment in time domain.Experiments on the algorithm of SMS4 show that the effectiveness of the maximum mutual information coefficient attack in the frequency domain is extended to the method of the side channel energy analysis.